A new situation assessment method for aerial targets based on linguistic fuzzy sets and trapezium clouds. (January 2023) - Jia, Qianlei; Hu, Jiayue; Zhang, Weiguo; Zhai, Shaobo; Li, Zhaoxing
Abstract: Situation assessment has attracted much attention. The chief aim of this paper is to research the problem from the perspective of multicriteria group decision-making (MCGDM). First of all, this paper expresses the threat information with linguistic fuzzy sets, including Atanassov's intuitionistic fuzzy sets (AIFSs), Atanassov's interval-valued intuitionistic fuzzy sets (AIVIFSs), and interval intuitionistic uncertain linguistic sets (IIULSs). Then, some relevant concepts and aggregation operators of trapezium clouds are proposed, meanwhile, a new approach that calculates the weights considering subjectivity and objectivity is presented with multi-objective programming. Next, the conversion methods between AIFSs, AIVIFSs, IIULSs and trapezium clouds are derived. Finally, the algorithm process is presented and an illustrative example is employed to prove the validity. Also, the comparison analysis with other widely used methods is conducted to verify the feasibility of the proposed algorithm.